Unlocking the potential of V2O5 decorated on crossed g-C3N4 monolayers derived from synergistic bio-transformation of ZnMn2O4 for antibiotic photodegradation - Bahadoran, Ashkan; Nene Ajinkya; Sharghi, Mohammadreza; Hasanvandian, Farzad; Wang, Yan; Chen, Huiwen; Namvari, Mina; Kakavandi, Babak; Marsili, Enrico; Galluzzi, Massimiliano; Ramakrishna, Seeram (Journal of Materials Chemistry A, 2024)
Although the physiochemical merits of g-C3N4-based photocatalysts have garnered increasing interest in the fields of energy and environmental science, insufficient layer detachment has created a gap between fundamental research and practical applications. To unlock the intrinsic potential of g-C3N4, a bio-transformation of the ZnMn2O4 ((6)ZM) gel was employed to introduce highly-ordered modulation caused by steric hindrance during melamine pyrolysis. Phytomediated (6)ZM reorganized traditional carbon nitride into crossed C3N4 (CCN) monolayers, simultaneously engineering an auspicious Z-schematic system ((6)ZM/CCN). Phytoconverted (6)ZM retained the crystalline-amorphous configuration for facile charge transfer and provided a large surface area (288 m2 g−1) that was 2.3 times greater than that of thermally prepared g-C3N4 (TCN) monolayers. Additionally, (6)ZM exhibited a quantum confinement-promoted reduction capability and induced bulging on CCN monolayers to fully utilize photons through multilevel light scattering and reflection. Specific sequential two-step calcination of (6)ZM/CCN, furnishing affordable dual Z-schematic VO–(6)ZM/CCN, was specifically developed to introduce a third component into the structure without incurring additional operational cost or complexity. V2O5 (VO) nanoparticles were thermally anchored on (6)ZM/CCN to achieve highly efficient levofloxacin (LFC) detoxification under visible-light irradiation. After optimizing all effective synthesis parameters and experimental variables, VO–(6)ZM/CCN exhibited unsurpassed activity, achieving complete LFC photodegradation (50 mg L−1) within 120 min, which was 10.7, 8.7, and 24.7 times more kinetically efficient than the photodegradations achieved by (6)ZM, TCN, and VO, respectively. The outstanding performance of VO–(6)ZM/CCN was evident through complete mineralization of LFC, excellent decontamination of pharmaceutical wastewater within 300 min, resistance to performance deterioration during successive cycling runs, and the corresponding postcharacterization. The combination of simultaneous Z-scheme formation with photogenic (6)ZM provides a promising strategy to bridge the gap between experimental investigations and industrial applications of g-C3N4.